Recent progress in the device architecture of white quantum-dot light-emitting diodes. Issue 4 (2nd October 2019) - Zhang, Heng; Su, Qiang; Chen, Shuming
Abstract : White-light-emission quantum dot light-emitting diodes (WQLEDs) have attracted great attention of late because they could have potential applications in both flat-panel displays and solid-state lighting due to their advantages of tunable emission spectra, low driving voltage, high luminous efficiency, and high brightness. Over the past decades, with the rapid development of both quantum dot (QD) materials and device structures, WQLEDs have achieved tremendous progress. This review investigates the influence of device architectures on the performance of WQLEDs. The importance and status of the WQLEDs based on CdSe-QDs are first discussed. Then WQLEDs with a mixed-QD single light emission layer (EML), a multilayered QD EML, and tandem structures are reviewed. WQLEDs based on cadmium-free QDs are also briefly introduced. Finally, the key challenges that WQLEDs are currently facing are identified, and some possible solutions are proposed for further developing stable and efficient WQLEDs.